DNA protection, antioxidant, antibacterial and enzyme inhibition activities of heartwood and sapwood extracts from juniper and olive woods - Özkan, Osman Emre; Zengin, Gökhan; Akça, Mehmet; Baloğlu, Mehmet Cengiz; Olgun, Çağrı; Altuner, Ergin Murat; Ateş, Saim; Aktümsek, Abdurrahman; Vurdu, Hasan (Royal Society of Chemistry (RSC), 2015)
In this study, DNA protective, antioxidant, antibacterial and enzyme inhibiting properties of methanol extracts obtained from juniper and olive heartwood and sapwood were determined.
Keywords: 13. Climate action; 7. Clean energy; 6. Clean water; 3. Good health